Assessing the predictive ability of sovereign default risk on exchange rate returns - Claudia Foroni; Francesco Ravazzolo; Barbara Sadaba (Bank of Canada, 2017)
Increased sovereign credit risk is often associated with sharp currency movements. Therefore, expectations of the probability of a sovereign default event can convey important information regarding future movements of exchange rates. In this paper, we investigate the possible pass-through of risk in the sovereign debt markets to currency markets by proposing a new risk premium factor for predicting exchange rate returns based on sovereign default risk. We compute it from the term structure at different maturities of sovereign credit default swaps and conduct an out-of-sample forecasting exercise to test whether we can improve upon the benchmark random walk model. Our results show that the inclusion of the default risk factor improves the forecasting accuracy upon the random walk model at short forecasting horizons.
Keywords: C22; C52; C53; F31; 330; Exchange rates; Econometric and statistical methods; International financial markets